Analisis Kesalahan Penggunaan Frasa pada Tajuk Rencana Surat Kabar Kompas - nfn Alber (Madah: Jurnal Bahasa dan Sastra, 2018)
Newspapers, as a medium of information read by various circles, have an important role in the development of the language of a nation. Meanwhile, in the local or national newspapers circulating, error in the use of phrases is still found. The error even occurred in the national newspaper level, in this case is Kompas. The error occurs because of lack of attention to the rules of language. Therefore, this study observes the error of using phrases in Kompas newspaper editorial. This study used prescriptive content analysis method. Data collection techniques are documentation and hermeneutic techniques. The research data is sourced from editorials of Kompas newspaper taken randomly. The data studied are documented by read, recorded, then summarized, and grouped by errors in the phrase field. Based on the analysis, the misuse of phrases in the editorials of Kompas newspapers is the use of excessive or wasteful elements and improper use of prepositions.